Ontario Municipal Policy Affecting Local Autonomy: A Case Study Involving Windsor and Toronto - Kulisek, Larry; Price, Trevor (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
During the first great burst of urban growth in Canada from the beginning of the 20th century and on into the 1920s it was generally the municipalities, either singly or collectively, which fostered policy innovation and new services. Provinces generally did little at that time, either to foster new policies or rein in local autonomy. It was only after the economic setbacks of the depression and a renewed spirit of urban development after 1945 that provincial direction over municipalities became much more significant.This paper is a case study of two major policy crises which threatened the viability of the whole municipal system in Ontario. In the 1930s the Border Cities (Metropolitan Windsor) faced bankruptcy and economic collapse and placed in jeopardy the credit of the province. In the early 1950s the inability of Metropolitan Toronto to create area-wide solutions to severe servicing problems threatened to stall the main engine of provincial growth.The case study demonstrates how a reluctant provincial government intervened to create new metropolitan arrangements for the two areas and accompanied this with a greatly expanded structure of provincial oversight including a strengthened Ontario Municipal Board and a specific department to handle municipal affairs. The objective of the policy was to bolster local government rather than to narrow municipal autonomy.